Three Solutions to Problems of Categorized Medical Nomenclatures - Dunham, G. S.; Henson, D. E.; Pacak, M. G. (Methods of Information in Medicine, 1984)
Three problems arising with the use and improvement of SNOP are discussed with their solutions: 1.) complete categorical encoding of disease; 2.) dual categorization of nomenclature terms; 3.) coding physiological function and dysfunction as a function and a topography. These solutions entail the expansion of the class of mathematical models for classified nomenclatures from tree hierarchies to partially ordered sets.
Keywords: Categorized Nomenclature; SNOP; SNOMED; Medical Lexicography; .Poset